Optimization of The Success Rate of The Epicotyl Grafting Method in Nutmeg with Different Rootstock Stages and Scion Leaf Numbers - Suhartanto, Mohamad Rahmad; Ruhnayat, Agus; Qadir, Abdul; Rostiana, Otih (Sains Natural: Journal of Biology and Chemistry, 2025)
The availability of seeds with known sex types is one of the obstacles in nutmeg cultivation. Epicotyl grafting using rootstocks aged 20–30 days is one of the solutions to overcome this issue. The objective of this study is to determine the optimal stage/age of rootstocks and the number of leaves of the scion to improve the success rate of nutmeg through epicotyl grafting. The experimental design used is a Randomized Block Design (RBD) with factorial pattern, repeated three times. The first factor is the stage of rootstock age, categorized as: 1 month (without leaves), 2 months (2 leaves), 3 months (3 leaves), and 4 months (4 leaves). The second factor is the number of leaves on the scion : 2 leaves cut in half, 2 leaves, and 3 leaves. Variables observation i.e. : a) C/N ratio in the rootstock and scion before grafting, b) plant morphology (Number of leaves, shoot length, shoot diameter, number of branches, and plant height.), and c) plant physiology (grafting success rate, graft union length, photosynthesis rate, and leaf chlorophyll content). The results showed that all rootstock stages and scion leaf number could be used for nutmeg grafting, with a 67-100% success rate. The best recommendation treatments are rootstocks with two leaves grafted to scions with two leaves, and rootstocks with four leaves grafted to scions with three leaves.